Nickel-based heterogeneous interface nano composite material for microwave thermal-power diagnosis and treatment integration
By developing nickel-based heterogeneous interface nanocomposites, using their high microwave absorption and dynamic therapy performance, the problems of poor absorption performance and poor diagnostic and therapeutic synergy in existing microwave thermotherapy technologies are solved, and efficient tumor microwave thermal-dynamic therapy and ultrasound imaging diagnosis are achieved.
Patent Information
- Application Number
- CN202311823002.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-06-27
Smart Images

Figure CN120204389A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technologies, and particularly to a nickel-based heterointerfacial nanocomposite material having strong absorption of microwaves in the medical frequency band, tumor microwave hyperthermia, microwave dynamic therapy, and ultrasonic imaging performance, and a preparation method and application thereof. Background Art
[0002] Due to the significant advantages of strong penetration ability and large tumor ablation range, microwave hyperthermia has attracted much attention in the field of tumor treatment. However, the main limitation faced by microwave hyperthermia is poor microwave absorption performance, resulting in a low electromagnetic energy to thermal energy conversion rate, which leads to incomplete tumor ablation and non-fatal thermal damage. These consequences will further cause a high recurrence of the lesion, especially for tumors with uneven shapes and high-risk locations. Conventional hyperthermia often damages the normal tissues around the tumor and is accompanied by serious postoperative complications such as fever, ulcers, or tissue necrosis. Therefore, developing new functional materials based on efficient microwave absorption in the medical frequency band to enhance various anti-tumor effects such as microwave thermal effects and microwave dynamics is an effective treatment strategy to balance the efficiency and safety of microwave hyperthermia, and is of great significance for microwave hyperthermia in the field of tumor diagnosis and treatment.
[0003] Moreover, in traditional treatment methods, diagnosis and treatment are two relatively independent processes. This is mainly because the delivery of contrast agents is a major problem. It is difficult to accurately deliver them to the target area, and excessive contrast agents will cause damage to normal tissues to a certain extent. In addition, the time difference between diagnosis and treatment will delay the treatment opportunity to a certain extent, unable to exert the best treatment effect, and the media used for diagnosis and treatment may affect each other. Summary of the Invention
[0004] To improve the deficiencies of the prior art, the present invention provides a nickel-based heterointerfacial nanocomposite material having high microwave absorption performance, microwave hyperthermia, microwave dynamic therapy, and ultrasonic imaging diagnosis functions in the medical frequency band, and a preparation method and application thereof. The nickel-based heterointerfacial nanocomposite material of the present invention has the characteristics of high microwave absorption performance in the medical frequency band, and can also meet the function of ultrasonic imaging diagnosis on the basis of microwave hyperthermia and microwave dynamic therapy. The nickel-based heterointerfacial nanocomposite material of the present invention can organically combine multiple functional units to achieve the synergistic diagnosis and treatment of tumor microwave hyperthermia and microwave dynamic therapy under the guidance of real-time imaging diagnosis, which is of great significance for the clinical diagnosis and treatment application of tumors.
[0005] The object of the present invention is achieved by the following technical solutions:
[0006] A nickel-based heterointerfacial nanocomposite, the nickel-based heterointerfacial nanocomposite having a core-shell structure, including a core and a shell, the shell coating the surface of the core; the core includes a metal-organic framework material with nickel metal nanoparticles and transition metal nanoparticles loaded on the surface; the shell includes a covalent organic framework material.
[0007] According to an embodiment of the present invention, the heterointerfacial includes an interfacial structure formed between the metal-organic framework material and the nickel metal nanoparticles, and an interfacial structure formed between the metal-organic framework material and the covalent organic framework material.
[0008] According to an embodiment of the present invention, the nickel metal nanoparticles and the transition metal nanoparticles are dispersed and loaded on the surface of the metal-organic framework material in a satellite-like manner.
[0009] According to an embodiment of the present invention, the nickel metal nanoparticles are loaded on the surface of the metal-organic framework material after a displacement reaction with the transition metal nanoparticles loaded on the surface of the metal-organic framework material during the preparation process. Part of the transition metal nanoparticles are anchored and loaded on the surface of the metal-organic framework material through the electronegativity difference with the nickel metal nanoparticles, and part are directly loaded on the surface of the metal-organic framework material.
[0010] According to an embodiment of the present invention, the metal-organic framework material is connected to the covalent organic framework material through an imine bond. Specifically, the imine bond is formed through a Schiff base reaction between -NH2 on the surface of the metal-organic framework material and the covalent organic framework monomer containing an aldehyde group functional group for preparing the covalent organic framework material.
[0011] According to an embodiment of the present invention, the particle size of the nickel metal nanoparticles is 10 - 20 nm, such as 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm.
[0012] According to an embodiment of the present invention, the particle size of the transition metal nanoparticles is 5 - 10 nm, such as 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0013] According to an embodiment of the present invention, the transition metal nanoparticles are selected from at least one of ruthenium metal nanoparticles, platinum metal nanoparticles and palladium metal nanoparticles.
[0014] According to an embodiment of the present invention, the metal-organic framework material is selected from at least one of zirconium metal-organic framework materials, titanium metal-organic framework materials and gadolinium metal-organic framework materials.
[0015] According to an embodiment of the present invention, the organic ligand forming the metal-organic framework material is selected from amino-containing organic ligands, and the amino-containing organic ligand is selected from 2-aminoterephthalic acid.
[0016] According to an embodiment of the present invention, the metal salt forming the metal-organic framework material is selected from at least one of zirconium tetrachloride, titanium tetrachloride, and gadolinium trichloride.
[0017] According to an embodiment of the present invention, the particle size of the metal-organic framework material is 150 nm - 220 nm, for example, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, or 220 nm.
[0018] According to an embodiment of the present invention, the metal-organic framework material contains amino groups (-NH2).
[0019] According to an embodiment of the present invention, the covalent organic framework material is selected from imine-based covalent organic framework materials.
[0020] According to an embodiment of the present invention, the monomers forming the covalent organic framework material include covalent organic framework monomers containing amino functional groups and covalent organic framework monomers containing aldehyde functional groups.
[0021] According to an embodiment of the present invention, the mass ratio of the covalent organic framework monomer containing amino functional groups to the covalent organic framework monomer containing aldehyde functional groups is 1:0.5 - 1:2, for example, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.5, or 1:1.8.
[0022] According to an embodiment of the present invention, the covalent organic framework monomer containing amino functional groups is selected from 1,3,5-tris(4-aminophenyl)benzene.
[0023] According to an embodiment of the present invention, the covalent organic framework monomer containing aldehyde functional groups is selected from 2,5-dimethoxyterephthalaldehyde.
[0024] According to an embodiment of the present invention, in the nickel-based heterointerfacial nanocomposite, the mass fraction of nickel metal nanoparticles is 10% - 20%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.
[0025] According to an embodiment of the present invention, in the nickel-based heterointerfacial nanocomposite, the mass fraction of transition metal nanoparticles is 10% - 20%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.
[0026] According to an embodiment of the present invention, in the nickel-based heterointerfacial nanocomposite, the mass ratio of the metal-organic framework material is 40%-70%, such as 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68% or 70%.
[0027] According to an embodiment of the present invention, in the nickel-based heterointerfacial nanocomposite, the mass ratio of the covalent organic framework material is 10%-20%, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0028] According to an embodiment of the present invention, the particle size of the nickel-based heterointerfacial nanocomposite is 180-280 nm, such as 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm or 280 nm.
[0029] According to an embodiment of the present invention, the thickness of the outer shell is 5-40 nm, such as 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm or 40 nm.
[0030] According to an embodiment of the present invention, the particle size of the inner core is 160-240 nm, such as 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm or 240 nm.
[0031] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite has an octahedron-spherical morphology.
[0032] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite has good microwave absorption performance in the medical frequency band (the frequency band where the microwave frequency is 433 MHz-2450 MHz); it has good microwave thermal conversion performance under microwave irradiation at this frequency; and it can promote the transfer of electrons and energy under microwave irradiation and thus promote the generation of reactive oxygen species, having good microwave dynamic performance; at the same time, it can be used for ultrasonic imaging to guide the diagnosis and treatment of tumors in real time and can be effectively applied to the biomedical field.
[0033] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite has enhanced magnetic loss and dielectric loss properties, thus showing excellent microwave absorption performance in the medical frequency band, being able to be used as a good microwave absorption material in the medical frequency band, and at the same time can effectively enhance the microwave thermal effect and microwave dynamic performance.
[0034] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite has good microwave thermal conversion performance under microwave irradiation, is a good microwave thermal sensitizer, and can effectively kill tumor cells.
[0035] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite can promote electron and energy transfer under microwave irradiation, rapidly consume glutathione, and catalyze hydrogen peroxide to produce oxygen, which is beneficial to inhibiting the overexpression of glutathione and catalyzing the alleviation of hypoxia of hydrogen peroxide in the tumor microenvironment, cascadingly enhancing the generation of reactive oxygen species, inducing apoptosis of tumor cells, is a good microwave dynamic sensitizer, and can synergistically and specifically kill tumor cells with microwave hyperthermia.
[0036] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite can be used for ultrasonic imaging, can be used as a contrast agent, and can guide the diagnosis and treatment of tumors in real time.
[0037] The present invention also provides a preparation method of the above nickel-based heterointerfacial nanocomposite, and the method includes the following steps:
[0038] 1) Dispersing a metal-organic framework material and a transition metal salt in a solvent, and stirring to prepare a metal-organic framework material loaded with transition metal ions;
[0039] 2) Dispersing the metal-organic framework material loaded with transition metal ions obtained in step 1) and a reducing agent in a solvent, and stirring to prepare a metal-organic framework material loaded with transition metal nanoparticles;
[0040] 3) Mixing the metal-organic framework material loaded with transition metal nanoparticles obtained in step 2), an electroless nickel plating solution and a reducing agent, and reacting to prepare a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles;
[0041] 4) Optionally, mixing the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles obtained in step 3), a chemical bath solution and a reducing agent, and reacting to prepare a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles;
[0042] 5) Mixing the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles obtained in step 3) or step 4), an activator and a covalent organic framework monomer containing an amino group, and reacting;
[0043] 6) Mixing the reaction product obtained in step 5), an activator and a covalent organic framework monomer containing an aldehyde functional group, and reacting;
[0044] 7) Mix the reaction product of step 6), the activator, the covalent organic framework monomer containing amino groups, the covalent organic framework monomer containing aldehyde functional groups, and the catalyst, and react to obtain the nickel-based heterogeneous interface nanocomposite material.
[0045] According to an embodiment of the present invention, in step 1), the metal-organic framework material can be prepared by a method known in the art, obtained by purchasing through commercial channels, or prepared by the following method:
[0046] 1-1) Disperse the metal salt, the organic ligand, and the regulator in a solvent to obtain a mixed solution;
[0047] 1-2) Place the mixed solution of step 1-1) in a reaction kettle for solvothermal reaction to obtain the metal-organic framework material.
[0048] Among them, in step 1-1), the mass concentration of the metal salt is 1-30 mg / mL; the molar mass ratio (mol / g) of the metal salt to the organic ligand is 1:0.5-1:10; the molar mass ratio (mol / g) of the metal salt to the regulator is 1:1-1:50.
[0049] Among them, in step 1-1), the metal salt is selected from at least one of zirconium tetrachloride, titanium tetrachloride, and gadolinium trichloride, preferably zirconium tetrachloride. The organic ligand is selected from amino-containing organic ligands, and the amino-containing organic ligand is selected from 2-aminoterephthalic acid. The regulator is selected from at least one of acetic acid, water, benzoic acid, mercaptoacetic acid, and citric acid, preferably acetic acid and water. The solvent is selected from N,N-dimethylformamide, N,N-dimethylformamide-methanol, N,N-diethylformamide, and N,N-diethylformamide-methanol, preferably N,N-dimethylformamide.
[0050] Among them, in step 1-2), the temperature of the solvothermal reaction is 100-150 °C. The time of the solvothermal reaction is 2-48 hours.
[0051] According to an embodiment of the present invention, in step 1), the transition metal salt is selected from at least one of ruthenium trichloride, platinum dichloride, and palladium dichloride, preferably ruthenium trichloride.
[0052] According to an embodiment of the present invention, in step 1), the mass concentration of the transition metal salt is 10-300 mg / mL; preferably 30-90 mg / mL.
[0053] According to an embodiment of the present invention, in step 1), the solvent is selected from at least one of deionized water and N,N-dimethylformamide, preferably deionized water.
[0054] According to an embodiment of the present invention, in step 1), the mass ratio of the metal-organic framework material to the transition metal salt is 1:0.1 - 1:10, preferably 1:0.5 - 1:5.
[0055] According to an embodiment of the present invention, in step 1), the stirring is, for example, magnetic stirring.
[0056] According to an embodiment of the present invention, in step 1), the stirring time is 1 - 6 hours.
[0057] According to an embodiment of the present invention, in step 1), the stirring temperature is room temperature.
[0058] According to an embodiment of the present invention, in step 2), the reducing agent is selected from sodium borohydride and hydrazine hydrate, preferably sodium borohydride.
[0059] According to an embodiment of the present invention, in step 2), the mass ratio of the reducing agent to the metal-organic framework material loaded with transition metal ions is 1:0.1 - 1:50, preferably 1:1 - 1:20.
[0060] According to an embodiment of the present invention, in step 2), the stirring temperature is 50 - 80 °C.
[0061] According to an embodiment of the present invention, in step 2), the stirring is, for example, magnetic stirring.
[0062] According to an embodiment of the present invention, in step 2), the stirring time is 1 - 6 hours.
[0063] According to an embodiment of the present invention, in step 2), the metal-organic framework material loaded with transition metal ions obtained in step 1) is dispersed in a solvent and magnetically stirred at 50 - 80 °C; the reducing agent is dispersed in the same solvent; the reducing agent solution is added to the dispersion of the metal-organic framework material loaded with transition metal ions, and stirred to obtain a metal-organic framework material loaded with transition metal nanoparticles.
[0064] According to an embodiment of the present invention, in step 2), after adding the reducing agent, the reducing agent can reduce the transition metal ions loaded on the surface of the metal-organic framework material into transition metal nanoparticles, and a metal-organic framework material loaded with transition metal nanoparticles is obtained.
[0065] According to an embodiment of the present invention, in step 3), the electroless nickel plating solution includes nickel chloride, sodium citrate, maleic acid, sodium hydroxide and deionized water. In the electroless nickel plating solution, the concentration of nickel chloride is 5 mg / mL - 40 mg / mL, such as 10 mg / mL, 15 mg / mL, 20 mg / mL or 30 mg / mL; the concentration of sodium citrate is 10 mg / mL - 50 mg / mL, such as 20 mg / mL, 25 mg / mL, 30 mg / mL or 40 mg / mL; the concentration of maleic acid is 1 mg / mL - 20 mg / mL, such as 5 mg / mL, 8 mg / mL, 10 mg / mL or 15 mg / mL; the concentration of sodium hydroxide is 5 mg / mL - 30 mg / mL, such as 10 mg / mL, 15 mg / mL, 20 mg / mL or 25 mg / mL.
[0066] According to an embodiment of the present invention, in step 3), the reducing agent is selected from sodium borohydride and hydrazine hydrate, and preferably hydrazine hydrate.
[0067] According to an embodiment of the present invention, in step 3), the concentration of the reducing agent is 0.05 - 0.2 mg / mL.
[0068] According to an embodiment of the present invention, in step 3), the reaction time is 1 - 4 hours.
[0069] According to an embodiment of the present invention, in step 3), the reaction temperature is 70 - 90 °C.
[0070] According to an embodiment of the present invention, in step 3), the metal-organic framework material loaded with transition metal nanoparticles is dispersed in a solvent; then it is added to the electroless nickel plating solution at 70 - 90 °C, and then a reducing agent is added. After reacting for 1 - 4 hours, it is taken out and placed in cold water, and cooled to room temperature to obtain a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles.
[0071] According to an embodiment of the present invention, in step 3), when the metal-organic framework material loaded with transition metal nanoparticles in step 2) is mixed with the electroless nickel plating solution and the reducing agent for a displacement reaction, part of the transition metal nanoparticles are replaced with nickel metal nanoparticles to obtain a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles.
[0072] According to an embodiment of the present invention, in step 4), the chemical bath solution comprises a transition metal salt, sodium citrate, maleic acid, sodium hydroxide and deionized water. In the chemical bath solution, the concentration of the transition metal salt is 2.5 mg / mL - 20 mg / mL, such as 5 mg / mL, 8 mg / mL, 10 mg / mL or 15 mg / mL; the concentration of sodium citrate is 5 mg / mL - 25 mg / mL, such as 10 mg / mL, 12 mg / mL, 15 mg / mL or 20 mg / mL; the concentration of maleic acid is 0.5 mg / mL - 10 mg / mL, such as 1 mg / mL, 2 mg / mL, 5 mg / mL or 8 mg / mL; the concentration of sodium hydroxide is 1 mg / mL - 15 mg / mL, such as 2 mg / mL, 5 mg / mL, 8 mg / mL or 10 mg / mL. Among them, the transition metal salt is selected from at least one of ruthenium trichloride, platinum dichloride and palladium dichloride, and preferably ruthenium trichloride.
[0073] According to an embodiment of the present invention, in step 4), the reducing agent is selected from sodium borohydride and hydrazine hydrate, and preferably hydrazine hydrate.
[0074] According to an embodiment of the present invention, in step 4), the concentration of the reducing agent is 0.05 - 0.2 mg / mL.
[0075] According to an embodiment of the present invention, in step 4), the reaction time is 1 - 4 hours.
[0076] According to an embodiment of the present invention, in step 4), the reaction temperature is 70 - 90 °C.
[0077] According to an embodiment of the present invention, in step 4), the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles is dispersed in a solvent; then it is added to the chemical bath solution at 70 - 90 °C, after reacting for 1 - 4 hours, a reducing agent is added, and it is taken out and placed in cold water and cooled to room temperature to obtain the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles.
[0078] According to an embodiment of the present invention, the term "optionally" in step 4) means that this step can be carried out or not. In order to further increase the loading amount of transition metal nanoparticles in the composite material and enhance its effect, it is preferred to carry out step 4).
[0079] According to an embodiment of the present invention, in step 4), after mixing and reacting the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles with a chemical bath solution and a reducing agent, the electronegativity difference between the nickel metal nanoparticles and the transition metal nanoparticles formed from the transition metal salts in the chemical bath can be utilized to anchor and load the transition metal nanoparticles onto the surface of the metal-organic framework material; that is, there are two parts of transition metal nanoparticles on the surface of the metal-organic framework material. One part is the transition metal nanoparticles directly loaded onto the surface of the metal-organic framework material, and the other part is the transition metal nanoparticles directly anchored and loaded onto the surface of the metal-organic framework material through the electronegativity difference with the nickel metal nanoparticles. The two parts of transition metal nanoparticles can be the same or different.
[0080] According to an embodiment of the present invention, in step 5), the reaction time is 0.5 - 4 hours.
[0081] According to an embodiment of the present invention, in step 5), the reaction temperature is room temperature.
[0082] According to an embodiment of the present invention, in step 5), the reaction is carried out under stirring conditions. The stirring is, for example, mechanical stirring, and the rotation speed of the mechanical stirring is 50 - 300 r / min.
[0083] According to an embodiment of the present invention, in step 5), the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles and the activator are dispersed in an organic solvent, the covalent organic framework monomer containing an amino group is dispersed in an organic solvent, and then the dispersion of the covalent organic framework monomer containing an amino group is added to the dispersion of the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles and the activator for reaction.
[0084] According to an embodiment of the present invention, in step 5), the organic solvent is selected from acetonitrile and ethanol.
[0085] According to an embodiment of the present invention, in step 5), the activator is selected from polyvinylpyrrolidone.
[0086] According to an embodiment of the present invention, in step 5), the concentration of the dispersion of the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles is 1 mg / mL - 5 mg / mL, for example, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL or 4 mg / mL. The concentration of the dispersion of the covalent organic framework monomer containing an amino group is 0.5 mg / mL - 2 mg / mL, for example, 0.8 mg / mL, 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL or 1.8 mg / mL.
[0087] According to an embodiment of the present invention, in step 5), the mass ratio of the activator to the amino group-containing covalent organic framework monomer is 20:1 - 80:1, such as 30:1, 40:1, 50:1, 60:1 or 70:1.
[0088] According to an embodiment of the present invention, in step 5), the mass ratio of the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles to the amino group-containing covalent organic framework monomer is 1:1 - 20:1, such as 2:1, 5:1, 8:1, 10:1, 12:1, 15:1 or 18:1.
[0089] According to an embodiment of the present invention, in step 5), after the reaction is completed, it is preferred to obtain the reaction product by centrifugal separation, washing and drying.
[0090] According to an embodiment of the present invention, in step 6), the reaction time is 0.5 - 4 hours.
[0091] According to an embodiment of the present invention, in step 6), the reaction temperature is room temperature.
[0092] According to an embodiment of the present invention, in step 6), the reaction is carried out under stirring conditions. The stirring is, for example, mechanical stirring, and the rotation speed of the mechanical stirring is 50 - 300 r / min.
[0093] According to an embodiment of the present invention, in step 6), the reaction product of step 5) and the activator are dispersed in an organic solvent, the covalent organic framework monomer containing an aldehyde functional group is dispersed in an organic solvent, and then the dispersion of the covalent organic framework monomer containing an aldehyde functional group is added to the dispersion of the reaction product of step 5) and the activator for reaction.
[0094] According to an embodiment of the present invention, in step 6), the organic solvent is selected from acetonitrile.
[0095] According to an embodiment of the present invention, in step 6), the activator is selected from polyvinylpyrrolidone.
[0096] According to an embodiment of the present invention, in step 6), the concentration of the dispersion of the covalent organic framework monomer containing an aldehyde functional group is 0.5 mg / mL - 2 mg / mL, such as 0.8 mg / mL, 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL or 1.8 mg / mL. The concentration of the dispersion of the reaction product of step 5) is 1 mg / mL - 5 mg / mL, such as 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL or 4 mg / mL.
[0097] According to an embodiment of the present invention, in step 6), the mass ratio of the covalent organic framework monomer containing an amino functional group to the covalent organic framework monomer containing an aldehyde functional group is 1:0.5 - 1:2.
[0098] According to an embodiment of the present invention, in step 6), the mass ratio of the activator to the covalent organic framework monomer containing an aldehyde group is 1:1 - 20:1, for example, 2:1, 5:1, 8:1, 10:1, 12:1, 15:1 or 18:1.
[0099] According to an embodiment of the present invention, in step 6), after the reaction is completed, it is preferably centrifuged, washed and dried to obtain the reaction product.
[0100] According to an embodiment of the present invention, in step 7), the reaction time is 2 - 12 hours.
[0101] According to an embodiment of the present invention, in step 7), the reaction temperature is room temperature.
[0102] According to an embodiment of the present invention, in step 7), the reaction is carried out under stirring conditions. The stirring is, for example, mechanical stirring, and the rotation speed of the mechanical stirring is 50 - 300 r / min.
[0103] According to an embodiment of the present invention, in step 7), the reaction product of step 6) and the activator are dispersed in an organic solvent, and then the dispersion of the covalent organic framework monomer containing an amino group, the dispersion of the covalent organic framework monomer containing an aldehyde functional group and the catalyst are added to the dispersion of the reaction product of step 6) and the activator for reaction.
[0104] According to an embodiment of the present invention, in step 7), the organic solvent is selected from acetonitrile and ethanol.
[0105] According to an embodiment of the present invention, in step 7), the activator is selected from polyvinylpyrrolidone.
[0106] According to an embodiment of the present invention, in step 7), the concentration of the dispersion of the reaction product of step 6) is 1 mg / mL - 5 mg / mL, for example, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL or 4 mg / mL.
[0107] According to an embodiment of the present invention, in step 7), the catalyst is selected from acetic acid.
[0108] According to an embodiment of the present invention, in step 7), the addition amount of the covalent organic framework monomer containing an amino functional group is the same as the addition amount of the covalent organic framework monomer containing an amino functional group in step 5).
[0109] According to an embodiment of the present invention, in step 7), the addition amount of the covalent organic framework monomer containing an aldehyde functional group is the same as that of the covalent organic framework monomer containing an aldehyde functional group in step 6).
[0110] According to an embodiment of the present invention, in step 7), after the reaction is completed, it is preferable to obtain the reaction product by centrifugal separation, washing and drying.
[0111] The present invention also provides an application of the above nickel-based heterointerfacial nanocomposite in a microwave diagnosis and treatment preparation.
[0112] According to an embodiment of the present invention, the application of the nickel-based heterointerfacial nanocomposite in a microwave hyperthermia preparation (such as a microwave hyperthermia sensitizer).
[0113] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite is dispersed in physiological saline to prepare a dispersion with a concentration of 0 - 5 mg / mL, and the temperature change is recorded under microwave irradiation.
[0114] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite and a paraffin matrix are uniformly mixed and pressed into a columnar ring with a mass fraction of the nickel-based heterointerfacial nanocomposite of 20% - 60% and a thickness of 1 - 8 mm, and various electromagnetic parameters are measured and recorded using a vector network analyzer.
[0115] According to an embodiment of the present invention, the application of the nickel-based heterointerfacial nanocomposite in a microwave dynamic therapy preparation (such as a microwave dynamic sensitizer).
[0116] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite is dispersed in a buffer solution to prepare a dispersion of 0 - 5 mg / mL, and a detection indicator is added under the condition of having or not having hydrogen peroxide. After microwave irradiation, it is left standing for 5 - 120 min, and the level of reactive oxygen species generated is detected.
[0117] The present invention also provides an application of the above nickel-based heterointerfacial nanocomposite in a contrast agent (such as an ultrasonic imaging preparation).
[0118] According to an embodiment of the present invention, the nickel-based heterointerfacial nanocomposite is dispersed in physiological saline with a mass fraction of 0.9% to prepare a mixed solution with a concentration of 0 - 5 mg / mL for in vitro ultrasonic imaging.
[0119] The present invention also provides a preparation, and the preparation includes the above nickel-based heterointerfacial nanocomposite.
[0120] According to an embodiment of the present invention, the preparation is a microwave diagnosis and treatment preparation or a contrast agent.
[0121] According to an embodiment of the present invention, the microwave diagnosis and treatment preparation is a microwave hyperthermia preparation or a microwave dynamic therapy preparation.
[0122] According to an embodiment of the present invention, the microwave diagnosis and treatment preparation is a tumor microwave diagnosis and treatment preparation.
[0123] According to an embodiment of the present invention, the contrast agent is an ultrasonic imaging preparation.
[0124] Advantages of the present invention:
[0125] (1) In the present invention, nickel metal nanoparticles are loaded on a metal-organic framework, introducing magnetic loss properties mainly based on natural resonance and eddy current loss, thereby shifting the microwave absorption performance to the medical frequency band. Then, through nanoengineering, a multi-layered heterojunction interface (the heterojunction interface between the metal-organic framework material and the nickel metal nanoparticles and the heterojunction interface between the metal-organic framework material and the covalent organic framework material) is constructed in the nickel-based heterojunction interface nanocomposite, enhancing the dielectric loss performance dominated by interfacial polarization and further improving the intensity of microwave absorption.
[0126] (2) The nickel-based heterojunction interface nanocomposite of the present invention is used in the field of microwave diagnosis and treatment preparations. First, the nickel-based heterojunction interface nanocomposite has good biosecurity and can be widely applied in vivo. Second, the nickel-based heterojunction interface nanocomposite has excellent microwave absorption performance in the medical frequency band, and it has a high microwave thermal conversion efficiency under microwave irradiation, killing tumor cells through high temperature. Then, under the stimulation of microwave response, the nickel-based heterojunction interface nanocomposite can promote the transfer of electrons and energy, enhance the ability to generate reactive oxygen species, accelerate the apoptosis of tumor cells, and is beneficial to the synergistic treatment of microwave hyperthermia and microwave dynamic therapy.
[0127] (3) The nickel-based heterojunction interface nanocomposite of the present invention has good biocompatibility and controllable size, can easily target the tumor area through the enhanced permeability and retention effect of solid tumors, consume glutathione and hydrogen peroxide in the tumor microenvironment, effectively generate oxygen, regulate the high redox characteristics of the tumor microenvironment, improve the hypoxic environment, and further promote the synergistic treatment of microwave hyperthermia and microwave dynamic therapy. In addition, the ultrasonic imaging performance can be used for real-time imaging to guide tumor treatment, and the finally obtained microwave-responsive tumor diagnosis and treatment preparation can achieve the elimination of tumors under the guidance of real-time imaging, having good clinical application prospects.
[0128] In summary, the present invention provides a microwave diagnosis and treatment preparation based on nickel-based heterogeneous interface nanocomposites that responds to microwaves in the medical frequency band and integrates microwave hyperthermia, microwave dynamic therapy, and ultrasonic imaging. By loading nickel metal nanoparticles, magnetic loss properties mainly based on natural resonance and eddy current loss are introduced, thereby shifting the microwave absorption properties to the medical frequency band. Then, a multi-layer heterogeneous interface is constructed through nanoengineering to enhance the dielectric loss properties dominated by interfacial polarization, further improving the intensity of microwave absorption. At the same time, the increase in microwave absorption intensity not only enhances the microwave thermal effect of microwave hyperthermia but also promotes the transfer of electrons and energy, further catalyzing the generation of reactive oxygen species and enhancing microwave dynamic therapy. Consuming glutathione and hydrogen peroxide in the tumor microenvironment can effectively generate oxygen, regulate the high redox characteristics of the tumor microenvironment, improve the hypoxic environment, and further promote the synergistic treatment of microwave hyperthermia and microwave dynamic therapy. In addition, loading transition metal nanoparticles with oxygen-producing functions can achieve real-time ultrasonic imaging to guide tumor treatment, realizing the integration of diagnosis and treatment, and having good application value. Description of the Drawings
[0129] Figure 1 Transmission electron microscope characterization diagram of the metal-organic framework (M) prepared in Example 1.
[0130] Figure 2 Transmission electron microscope characterization diagram of the metal-organic framework loaded with nickel metal nanoparticles (MRN) prepared in Example 7.
[0131] Figure 3 Transmission electron microscope characterization diagram of the metal-organic framework loaded with nickel metal nanoparticles and transition metal nanoparticles (MRNR) prepared in Example 10.
[0132] Figure 4 Transmission electron microscope characterization diagram of the nickel-based heterogeneous interface nanocomposite (MRNRC) prepared in Example 12.
[0133] Figure 5 Three-dimensional reflection loss schematic diagram of the metal-organic framework (M) prepared in Example 1.
[0134] Figure 6 Three-dimensional reflection loss schematic diagram of the nickel-based heterogeneous interface nanocomposite (MRNRC) prepared in Example 12.
[0135] Figure 7 Schematic diagram of the microwave heating curve of the metal-organic framework (M) prepared in Example 1 in physiological saline.
[0136] Figure 8 Schematic diagram of the microwave heating curve of the nickel-based heterogeneous interface nanocomposite (MRNRC) prepared in Example 12 in physiological saline.
[0137] Figure 9 Comparison of the heating effect of the metal-organic framework (M) prepared in Example 1 and the nickel-based heterointerfacial nanocomposite (MRNRC) prepared in Example 12.
[0138] Figure 10 Schematic diagram for characterizing the microwave dynamic performance of the metal-organic framework material (M) prepared in Example 1 and the nickel-based heterointerfacial nanocomposite (MRNRC) prepared in Example 12.
[0139] Figure 11 Schematic diagram of in vitro ultrasound imaging of the metal-organic framework material (MRN) loaded with Ru-Ni metal nanoparticles prepared in Example 7.
[0140] Figure 12 Schematic diagram of in vitro ultrasound imaging of the nickel-based heterointerfacial nanocomposite (MRNRC) prepared in Example 12. Detailed implementation manners
[0141] The preparation method of the present invention will be further described in detail below with reference to specific examples. It should be understood that the following examples are only for illustrative and explanatory purposes of the present invention, and should not be construed as limiting the protection scope of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection of the present invention.
[0142] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; unless otherwise specified, the reagents, materials, etc. used in the following examples can all be obtained from commercial channels.
[0143] Example 1
[0144] Take 186 mg of zirconium tetrachloride, 145 mg of 2-aminoterephthalic acid, and 6 mL of acetic acid, add them to 50 mL of N,N-dimethylformamide and 0.5 mL of water, and disperse them evenly by ultrasonic treatment.
[0145] Place the mixed solution in a reaction kettle and react in an oven at 120 °C for 24 h.
[0146] After cooling to room temperature, centrifuge, and then wash once with water and ethanol respectively to prepare a metal-organic framework material.
[0147] The metal-organic framework material prepared in Example 1 was characterized by transmission electron microscopy, and the particle size observed by transmission electron microscopy was 175 nm.
[0148] Example 2
[0149] 1) The same as Example 1.
[0150] 2) Disperse 30 mg of the product obtained in step 1) in 9 mL of deionized water, stir magnetically at room temperature. Then, take 60 mg of platinum dichloride and add it to 1 mL of deionized water, and add it quickly. After 1 h, a metal-organic framework material loaded with Pt is obtained. 2+
[0151] 3) Disperse 30 mg of the product in step 2) in 9 mL of deionized water, stir magnetically in a water bath at 70 °C. Then, take 10 mg of sodium borohydride and add it to 1 mL of deionized water, and add it quickly. Reduce Pt 2+ to Pt metal nanoparticles, thereby obtaining a metal-organic framework material loaded with Pt metal nanoparticles.
[0152] The metal-organic framework material loaded with Pt metal nanoparticles prepared in Example 2 was characterized by transmission electron microscopy. The particle size observed by transmission electron microscopy was 185 nm.
[0153] Example 3
[0154] 1) The same as Example 1.
[0155] 2) Disperse 30 mg of the product obtained in step 1) in 9 mL of deionized water, stir magnetically at room temperature. Then, take 30 mg of ruthenium trichloride and add it to 1 mL of deionized water, and add it quickly. After 1 h, a metal-organic framework loaded with Ru 3+ is obtained.
[0156] 3) Disperse 30 mg of the product in step 2) in 9 mL of deionized water, stir magnetically in a water bath at 70 °C. Then, take 5 mg of sodium borohydride and add it to 1 mL of deionized water, and add it quickly. Reduce Ru 3+ to Ru metal nanoparticles, thereby obtaining a metal-organic framework material loaded with Ru metal nanoparticles.
[0157] The metal-organic framework material loaded with Ru metal nanoparticles prepared in Example 3 was characterized by transmission electron microscopy. The particle size observed by transmission electron microscopy was 189 nm.
[0158] Example 4
[0159] 1) The same as Example 1.
[0160] 2) Disperse 30 mg of the product obtained in step 1) in 9 mL of deionized water, stir magnetically at room temperature. Then, take 60 mg of ruthenium trichloride and add it to 1 mL of deionized water, and add it quickly. After 1 h, a metal-organic framework loaded with Ru 3+ is obtained.
[0161] 3) Disperse 30 mg of the product in step 2) into 9 mL of deionized water, stir magnetically in a water bath at 70 °C. Then, take 10 mg of sodium borohydride, add it to 1 mL of deionized water, add it quickly, and reduce Ru 3+ to Ru metal nanoparticles, thereby obtaining a metal-organic framework material loaded with Ru metal nanoparticles.
[0162] The metal-organic framework material loaded with Ru metal nanoparticles prepared in Example 4 was characterized by transmission electron microscopy. The particle size observed by transmission electron microscopy was 195 nm.
[0163] In the metal-organic framework material loaded with Ru metal nanoparticles prepared in Example 4, the loading amount of Ru metal nanoparticles loaded on the surface of the metal-organic framework material was significantly higher than that of the metal-organic framework material loaded with Ru metal nanoparticles prepared in Example 3, which was the loading amount of Ru metal nanoparticles loaded on the surface of the metal-organic framework material. And the Ru metal nanoparticles with a high loading amount were beneficial to improving the loading amount of nickel metal nanoparticles loaded by subsequent replacement.
[0164] Example 5
[0165] 1) The same as Example 4.
[0166] 2) The same as Example 4.
[0167] 3) The same as Example 4.
[0168] 4) Take 262 mg of nickel chloride hexahydrate, 400 mg of sodium citrate, and 80 mg of maleic acid, disperse them in 10 mL of deionized water, then add 180 mg of sodium hydroxide to adjust the pH value to 11.2, place it in a water bath at 80 °C. Then, disperse 30 mg of the product obtained in step 3) in 1 mL of water, add it quickly, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature, thereby obtaining a metal-organic framework material loaded with Ru-Ni metal nanoparticles.
[0169] The metal-organic framework material loaded with Ru-Ni metal nanoparticles prepared in Example 5 was characterized by transmission electron microscopy. The particle size observed by transmission electron microscopy was 215 nm.
[0170] Example 6
[0171] 1) The same as Example 2.
[0172] 2) The same as Example 2.
[0173] 3) The same as Example 2.
[0174] 4) Dissolve 131 mg of nickel chloride hexahydrate, 200 mg of sodium citrate, and 40 mg of maleic acid in 10 mL of deionized water. Then add 70 mg of sodium hydroxide to adjust the pH value to 9.5. Place it in an 80°C water bath. Then disperse 30 mg of the product obtained in step 3) in 1 mL of water, quickly add it, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature to obtain a metal-organic framework material loaded with Pt-Ni metal nanoparticles.
[0175] Characterize the metal-organic framework material loaded with Pt-Ni metal nanoparticles prepared in Example 6 by transmission electron microscopy. It can be known from energy spectrum testing that Pt metal nanoparticles and Ni metal nanoparticles are loaded on the surface of the metal-organic framework material, and the two are dispersed in a satellite shape and loaded on the surface of the metal-organic framework material. Among them, the particle size of the Ni metal nanoparticles is 16 nm; at the same time, the metal-organic framework material loaded with Pt-Ni metal nanoparticles is evenly dispersed, and the particle size of the metal-organic framework material loaded with Pt-Ni metal nanoparticles is 201 nm. The characterization results prove that the metal-organic framework material loaded with Pt-Ni metal nanoparticles obtained in this example has a heterojunction structure.
[0176] Example 7
[0177] 1) The same as Example 4.
[0178] 2) The same as Example 4.
[0179] 3) The same as Example 4.
[0180] 4) Dissolve 131 mg of nickel chloride hexahydrate, 200 mg of sodium citrate, and 40 mg of maleic acid in 10 mL of deionized water. Then add 90 mg of sodium hydroxide to adjust the pH value to 11.2. Place it in an 80°C water bath. Then disperse 30 mg of the product obtained in step 3) in 1 mL of water, quickly add it, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature to obtain a metal-organic framework material loaded with Ru-Ni metal nanoparticles.
[0181] The metal-organic framework material loaded with Ru-Ni metal nanoparticles prepared in Example 7 was characterized by transmission electron microscopy. It can be known from energy spectrum testing that Ru metal nanoparticles and Ni metal nanoparticles were loaded on the surface of the metal-organic framework material, and the two were dispersed in a satellite-like manner and loaded on the surface of the metal-organic framework material. The particle size of the Ni metal nanoparticles was 18 nm. At the same time, the metal-organic framework material loaded with Ru-Ni metal nanoparticles was evenly dispersed, and the particle size of the metal-organic framework material loaded with Ru-Ni metal nanoparticles was 213 nm. The characterization results prove that the metal-organic framework material loaded with Ru-Ni metal nanoparticles obtained in this example has a heterogeneous interface structure.
[0182] Example 8
[0183] 1) The same as Example 7.
[0184] 2) The same as Example 7.
[0185] 3) The same as Example 7.
[0186] 4) The same as Example 7.
[0187] 5) Take 114 mg of ruthenium trichloride, 200 mg of sodium citrate, and 40 mg of maleic acid and disperse them in 10 mL of deionized water. Then add 120 mg of sodium hydroxide to adjust the pH value to 9.8. Place it in an 80 °C water bath. Then disperse 30 mg of the product obtained in step 4) in 1 mL of water, quickly add it, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature to obtain the metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles.
[0188] The metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles prepared in Example 8 was characterized by transmission electron microscopy, and the particle size observed by transmission electron microscopy was 220 nm.
[0189] Example 9
[0190] 1) The same as Example 6.
[0191] 2) The same as Example 6.
[0192] 3) The same as Example 6.
[0193] 4) The same as Example 6.
[0194] 5) Dissolve 114 mg of ruthenium trichloride, 200 mg of sodium citrate, and 40 mg of maleic acid in 10 mL of deionized water. Then add 150 mg of sodium hydroxide to adjust the pH value to 11.2. Place it in an 80°C water bath. Then disperse 30 mg of the product obtained in step 4) in 1 mL of water, quickly add it, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature to obtain a metal-organic framework material loaded with Pt-Ni-Ru metal nanoparticles.
[0195] The metal-organic framework material loaded with Pt-Ni-Ru metal nanoparticles prepared in Example 9 was characterized by transmission electron microscopy. The particle size observed by transmission electron microscopy was 208 nm.
[0196] Example 10
[0197] 1) The same as Example 7.
[0198] 2) The same as Example 7.
[0199] 3) The same as Example 7.
[0200] 4) The same as Example 7.
[0201] 5) Dissolve 57 mg of ruthenium trichloride, 100 mg of sodium citrate, and 20 mg of maleic acid in 10 mL of deionized water. Then add 60 mg of sodium hydroxide to adjust the pH value to 9.8. Place it in an 80°C water bath. Then disperse 30 mg of the product obtained in step 4) in 1 mL of water, quickly add it, and then add 0.125 mL of hydrazine hydrate. After reacting for 1 h, quickly place it in cold water and cool it to room temperature to obtain a metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles.
[0202] The metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles obtained in Example 10 was characterized. The metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles was evenly dispersed, with a particle size of 219 nm. The surface of the metal-organic framework material was loaded with Ni metal nanoparticles and Ru metal nanoparticles dispersed in a satellite shape. The particle size of the Ni metal nanoparticles was 18 nm. The characterization results prove that the metal-organic framework material loaded with Ru-Ni-Ru metal nanoparticles obtained in this example has a heterogeneous interface structure.
[0203] Example 11
[0204] 1) The same as Example 9.
[0205] 2) The same as Example 9.
[0206] 3) The same as Example 9.
[0207] 4) The same as Example 9.
[0208] 5) The same as Example 9.
[0209] 6) Take 60 mg of the product obtained in step 5) and 1200 mg of polyvinylpyrrolidone and disperse them in 30 mL of acetonitrile; then weigh 30 mg of 1,3,5-tris(4-aminophenyl)benzene and dissolve it in 30 mL of acetonitrile and 4 mL of ethanol, add it to the above solution, stir magnetically at room temperature for 1 h, and centrifuge and wash.
[0210] 7) Disperse 30 mg of the product obtained in step 6) in 30 mL of acetonitrile and add 1200 mg of polyvinylpyrrolidone. Then weigh 26 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde and dissolve it in 30 ml of acetonitrile, add it to the above solution, stir magnetically at room temperature for 1 h, and centrifuge and wash.
[0211] 8) Disperse the product obtained in step 7) in 30 mL of acetonitrile and add 1200 mg of polyvinylpyrrolidone. Weigh 30 mg of 1,3,5-tris(4-aminophenyl)benzene and dissolve it in 30 mL of acetonitrile and 4 mL of ethanol, add it to the above solution. Then weigh 26 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde and dissolve it in 30 ml of acetonitrile, add it to the above solution. At the same time, add 200 μL of acetic acid, stir magnetically at room temperature for 12 h, centrifuge and wash to obtain a heterogeneous interface nanocomposite loaded with Pt-Ni-Ru metal nanoparticles.
[0212] Characterization by transmission electron microscopy: The heterogeneous interface nanocomposite loaded with Pt-Ni-Ru metal nanoparticles obtained in Example 11 was characterized. The heterogeneous interface nanocomposite loaded with Pt-Ni-Ru metal nanoparticles was evenly dispersed, with a particle size of 239 nm. Pt metal nanoparticles, Ni metal nanoparticles, and Ru metal nanoparticles were dispersed in a satellite-like manner on the surface of the metal-organic framework material, and the core was completely coated by the outer shell layer. The particle size of the Ni metal nanoparticles was 16 nm, and the thickness of the outer shell layer was 31 nm. The characterization results prove that the heterogeneous interface nanocomposite loaded with Pt-Ni-Ru metal nanoparticles obtained in this example has a heterogeneous interface structure.
[0213] Example 12
[0214] 1) The same as Example 10.
[0215] 2) The same as Example 10.
[0216] 3) The same as Example 10.
[0217] 4) The same as Example 10.
[0218] 5) The same as Example 10.
[0219] 6) Disperse 60 mg of the product obtained in step 5) and 1200 mg of polyvinylpyrrolidone in 30 mL of acetonitrile; then weigh 30 mg of 1,3,5-tris(4-aminophenyl)benzene and dissolve it in 30 mL of acetonitrile and 4 mL of ethanol, and add it to the above solution. Stir magnetically at room temperature for 1 h, and then centrifuge and wash.
[0220] 7) Disperse 60 mg of the product obtained in step 6) in 30 mL of acetonitrile and add 1200 mg of polyvinylpyrrolidone. Then weigh 26 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde and dissolve it in 30 mL of acetonitrile, and add it to the above solution. Stir magnetically at room temperature for 1 h, and then centrifuge and wash.
[0221] 8) Disperse 60 mg of the product obtained in step 7) in 30 mL of acetonitrile and add 1200 mg of polyvinylpyrrolidone. Weigh 30 mg of 1,3,5-tris(4-aminophenyl)benzene and dissolve it in 30 mL of acetonitrile and 4 mL of ethanol, and add it to the above solution. Then weigh 26 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde and dissolve it in 30 mL of acetonitrile, and add it to the above solution. At the same time, add 200 μL of acetic acid. Stir magnetically at room temperature for 12 h, and then centrifuge and wash to obtain the nickel-based heterointerfacial nanocomposite.
[0222] Characterization by transmission electron microscopy: The nickel-based heterointerfacial nanocomposite obtained in Example 12 was characterized. The nickel-based heterointerfacial nanocomposite was uniformly dispersed, with a particle size of 253 nm. The metal-organic framework material was dispersed in a satellite-like manner on the surface and loaded with Ni metal nanoparticles and Ru metal nanoparticles. The core was completely coated by the outer shell layer. The particle size of the Ni metal nanoparticles was 18 nm, and the thickness of the outer shell layer was 34 nm. The characterization results prove that the nickel-based heterointerfacial nanocomposite obtained in this example has a heterointerfacial structure.
[0223] Test Example 1
[0224] The materials prepared in Examples 1, 4, 7, 10, and 12 were tested for in vitro microwave thermal conversion performance. The specific experimental method is as follows:
[0225] 1) Add paraffin to a glass cup respectively and melt it in a water bath at 80 °C;
[0226] 2) Respectively take the materials prepared in Examples 1, 4, 7, 10, and 12 and add them to step 1), and press to obtain columnar rings with mass fractions of 20%, 40%, and 60% and a thickness of 1 - 8 mm, a total of 15;
[0227] 3) Use a vector network analyzer to measure and calculate the reflection loss value based on the transmission line theory to evaluate the microwave absorption performance.
[0228] Test example 1 proves that the materials prepared in Examples 1 and 4 have no microwave absorption performance in the medical frequency band; the materials prepared in Examples 7 and 10 have certain microwave absorption performance. This is because magnetic nickel metal nanoparticles are loaded through a displacement reaction, introducing magnetic loss mechanisms of natural resonance and eddy current loss, and constructing a heterogeneous interface of MOF-Ni, enhancing the dielectric loss mechanism of interfacial polarization, and shifting the microwave absorption peak towards the medical frequency band; the nickel-based heterogeneous interface nanocomposite prepared in Example 12 has strong microwave absorption performance, mainly because the composite material is coated with a COF shell on the surface, constructing a heterogeneous interface of MOF@COF through nanoengineering, and the inhomogeneity of the COF shell structure also enhances the anisotropy of the composite material, further improving the magnetic loss and dielectric loss. It can be seen that the nickel-based heterogeneous interface nanocomposite of the present invention combines a dielectric and a magnetic metal, and significantly improves the microwave absorption performance through complementary loss mechanisms and significant interfacial effects.
[0229] Figure 5 Schematic diagram of the three-dimensional reflection loss of the metal-organic framework (M) prepared in Example 1. Figure 6 Schematic diagram of the three-dimensional reflection loss of the nickel-based heterogeneous interface nanocomposite (MRNRC) prepared in Example 12. As can be seen from Figure 5 and Figure 6 , M has no obvious microwave absorption peak in the medical frequency band, while MRNRC has an obvious microwave absorption peak in the medical frequency band, and the peak value is less than -10 dB (microwave absorption rate is greater than 90%), indicating that MRNRC has excellent microwave absorption performance in the medical frequency band.
[0230] Test example 2
[0231] The materials prepared in Examples 1, 4, 7, 10, and 12 were tested for in vitro microwave thermal conversion performance. The specific experimental method is as follows:
[0232] 1) Dissolve sodium chloride in deionized water to prepare physiological saline (0.9% NaCl);
[0233] 2) Respectively take the materials prepared in Examples 1, 4, 7, 10, and 12 and add them to physiological saline to prepare solutions with concentrations of 0, 1 mg / mL, 2.5 mg / mL, and 5 mg / mL, respectively, and a total of 20 groups of solutions are obtained;
[0234] 3) Irradiate the solution with microwave for 5 min, and monitor the solution concentration in real time through a near-infrared thermal imager.
[0235] Test Example 2 proves that the materials prepared in Examples 1 and 4 have little difference in microwave heating effect from normal saline due to their lack of microwave absorption performance in the medical frequency band; the materials prepared in Examples 7 and 10 have certain microwave absorption performance in the medical frequency band, and can convert electromagnetic energy into heat energy, but the microwave heating effect is not strong; the nickel-based heterojunction interface nanocomposite material prepared in Example 12 has good microwave thermal conversion performance, and by responding to microwave radiation in the medical frequency band, the enhancement of microwave absorption performance can further improve the microwave thermal conversion efficiency, resulting in a significant microwave heating effect.
[0236] Figure 7 Schematic diagram of the microwave heating curve of the metal-organic framework (M) prepared in Example 1 in normal saline. From Figure 7 it can be seen that the microwave heating effect of M in normal saline is not very strong.
[0237] Figure 8 Schematic diagram of the microwave heating curve of the nickel-based heterojunction interface nanocomposite material (MRNRC) prepared in Example 12 in normal saline. From Figure 8 it can be seen that the microwave heating effect of MRNRC in normal saline is obvious, and shows concentration and time dependence.
[0238] Figure 9 Comparison of the heating effects of the metal-organic framework (M) prepared in Example 1 and the nickel-based heterojunction interface nanocomposite material (MRNRC) prepared in Example 12. From Figure 9 it can be seen that by comparing the microwave heating effects of M and MRNRC, it can be proved that MRNRC has good microwave thermal conversion performance, and by responding to microwave radiation in the medical frequency band, the enhancement of microwave absorption performance can further improve the microwave thermal conversion efficiency, resulting in a significant microwave heating effect.
[0239] Test Example 3
[0240] The materials prepared in Examples 1, 4, 7, 10 and 12 were subjected to in vitro microwave dynamic performance tests. The specific experimental methods are as follows:
[0241] 1) Respectively take the materials prepared in Examples 1, 4, 7, 10 and 12 and add them to phosphate buffered saline (pH = 7.2) to prepare a solution with a concentration of 0.5 mg / mL;
[0242] 2) Add 100 μM hydrogen peroxide to the solution;
[0243] 3) Add 10 μM reactive oxygen species detection probe DCFH-DA to the solution;
[0244] 4) Irradiate the solution with microwave for 5 min;
[0245] 5) After standing in the dark for 2 h, centrifuge and take the supernatant;
[0246] 6) Detect the fluorescence intensity at 520 nm under excitation at a wavelength of 480 nm.
[0247] Test Example 3 proves that the material prepared in Example 1 does not have microwave dynamic performance; the material prepared in Example 4 has microwave dynamic performance; the material prepared in Example 7 has a decrease in microwave dynamic performance due to the replacement reaction to load nickel metal nanoparticles; the material prepared in Example 10 has an enhanced microwave dynamic performance through the anchoring effect generated by the electronegativity difference between nickel and ruthenium; the nickel-based heterojunction interface nanocomposite material prepared in Example 12 greatly enhances the microwave dynamic performance by coating a COF outer layer, and under microwave stimulation, due to the significant enhancement of the microwave absorption performance in the medical frequency band, it can promote the transfer of electrons and energy, further improving the efficiency of generating reactive oxygen species, and can be used for the synergistic diagnosis and treatment of microwave thermo-dynamic therapy of in vivo tumors.
[0248] Figure 10 Schematic diagram for the characterization of the microwave dynamic performance of the metal-organic framework material (M) prepared in Example 1 and the nickel-based heterojunction interface nanocomposite material (MRNRC) prepared in Example 12. Specifically, in Figure 10 , PBS + H2O2 is the phosphate buffer blank group without microwave irradiation, PBS + H2O2 + MW is the phosphate buffer blank group with microwave irradiation, M + H2O2 is the control group of the metal-organic framework material prepared in Example 1 without microwave irradiation, M + H2O2 + MW is the control group of the metal-organic framework material prepared in Example 1 with microwave irradiation, MRNRC + H2O2 is the group of the nickel-based heterojunction interface nanocomposite material prepared in Example 12 without microwave irradiation, and MRNRC + H2O2 + MW is the group of the nickel-based heterojunction interface nanocomposite material prepared in Example 12 with microwave irradiation. It can be seen from Figure 10 that due to the significant enhancement of the microwave absorption performance in the medical frequency band, MRNRC can promote the transfer of electrons and energy under microwave stimulation, further improving the efficiency of generating reactive oxygen species, and can be used for the synergistic diagnosis and treatment of microwave thermo-dynamic therapy of in vivo tumors.
[0249] Test Example 4
[0250] Perform in vitro ultrasonic imaging tests on the materials prepared in Examples 1, 4, 7, 10, and 12.
[0251] The specific experimental method is as follows:
[0252] 1) Respectively take the materials prepared in Examples 1, 4, 7, 10, and 12 and add them to 0.9% physiological saline to prepare a solution with a concentration of 5.0 mg / mL;
[0253] 2) Inject the solution into the latex tube and irradiate the solution with microwaves for 5 min;
[0254] 3) Use an ultrasonic probe to detect ultrasonic images;
[0255] 4) Record the ultrasonic images corresponding to different concentrations respectively.
[0256] Test Example 4 proves that during the ultrasonic experiment, no enhancement effect of ultrasonic images was found for the materials prepared in Examples 1, 4, and 7; the material prepared in Example 10 has an ultrasonic image enhancement effect, but the imaging effect is not obvious and it is difficult to be used in practical applications; the nickel-based heterointerfacial nanocomposite material prepared in Example 12 has an extremely strong ultrasonic image enhancement effect, can effectively enhance the ultrasonic contrast function, and can be used for ultrasonic imaging.
[0257] Figure 11 It is a schematic diagram of in vitro ultrasonic imaging of the metal-organic framework material (MRN) loaded with Ru-Ni metal nanoparticles prepared in Example 7. Figure 11 In it, Control is normal saline, and no image enhancement effect occurs under the ultrasonic probe; MRN is the ultrasonic image observed after adding the metal-organic framework material loaded with Ru-Ni metal nanoparticles, and the image enhancement effect is weak.
[0258] Figure 12 It is a schematic diagram of in vitro ultrasonic imaging of the nickel-based heterointerfacial nanocomposite material (MRNRC) prepared in Example 12. Figure 12 In it, Control is normal saline, and no image enhancement effect occurs under the ultrasonic probe; MRNRC is the ultrasonic image observed after adding the nickel-based heterointerfacial nanocomposite material, and the image is significantly enhanced.
[0259] It can be seen from this that the nickel-based heterointerfacial nanocomposite material of the present invention has an effect on in vitro ultrasonic imaging.
[0260] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A nickel-based heterogeneous interface nanocomposite, the nickel-based heterogeneous interface nanocomposite having a core-shell structure, including a core and a shell, the shell coating the surface of the core; the core includes a metal-organic framework material with nickel metal nanoparticles and transition metal nanoparticles loaded on the surface; the shell includes a covalent organic framework material.
2. The composite material according to claim 1, wherein The nickel metal nanoparticles and the transition metal nanoparticles are dispersed and loaded on the surface of the metal-organic framework material in a satellite shape; and / or, the metal-organic framework material is connected to the covalent organic framework material through imine bonds. Preferably, the transition metal nanoparticles are selected from at least one of ruthenium metal nanoparticles, platinum metal nanoparticles, and palladium metal nanoparticles; and / or, the metal-organic framework material is selected from at least one of zirconium metal-organic framework materials, titanium metal-organic framework materials, and gadolinium metal-organic framework materials; and / or, the metal-organic framework material contains an amino group (-NH2); and / or, the organic ligand forming the metal-organic framework material is selected from amino-based organic ligands, and the amino-based organic ligands are selected from 2-aminoterephthalic acid. Preferably, the covalent organic framework material is selected from imine-based covalent organic framework materials; the monomers forming the covalent organic framework material include covalent organic framework monomers containing amino functional groups and covalent organic framework monomers containing aldehyde functional groups; and / or, the covalent organic framework monomer containing an amino functional group is selected from 1,3,5-tris(4-aminophenyl)benzene; the covalent organic framework monomer containing an aldehyde functional group is selected from 2,5-dimethoxyterephthalaldehyde.
3. The composite material according to claim 1 or 2, wherein In the nickel-based heterogeneous interface nanocomposite, the mass ratio of nickel metal nanoparticles is 10%-20%; and / or, in the nickel-based heterogeneous interface nanocomposite, the mass ratio of transition metal nanoparticles is 10%-20%; and / or, in the nickel-based heterogeneous interface nanocomposite, the mass ratio of the metal-organic framework material is 40%-70%; and / or, in the nickel-based heterogeneous interface nanocomposite, the mass ratio of the covalent organic framework material is 10%-20%. Preferably, the particle size of the nickel metal nanoparticles is 10-20 nm; and / or, the particle size of the transition metal nanoparticles is 5-10 nm; and / or, the particle size of the nickel-based heterogeneous interface nanocomposite is 180-280 nm; and / or, the particle size of the metal-organic framework material is 150 nm-220 nm; and / or, the thickness of the shell is 5-40 nm; and / or, the particle size of the core is 160-240 nm.
4. A method for preparing the nickel-based heterogeneous interface nanocomposite according to any one of claims 1-3, the method comprising the following steps: 1) Disperse the metal-organic framework material and the transition metal salt in a solvent, and stir to prepare a metal-organic framework material loaded with transition metal ions; 2) Disperse the metal-organic framework material loaded with transition metal ions in step 1) and a reducing agent in a solvent, and stir to prepare a metal-organic framework material loaded with transition metal nanoparticles; 3) Mix the metal-organic framework material loaded with transition metal nanoparticles, electroless nickel plating solution, and reducing agent in step 2), and react to prepare a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles; 4) Optionally, mix the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles, chemical bath solution, and reducing agent in step 3), and react to prepare a metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles; 5) Mix the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles, activator, and amino group-containing covalent organic framework monomer in step 3) or step 4), and react; 6) Mix the reaction product in step 5), activator, and aldehyde group-containing covalent organic framework monomer, and react; 7) Mix the reaction product in step 6), activator, amino group-containing covalent organic framework monomer, aldehyde group-containing covalent organic framework monomer, and catalyst, and react to prepare the nickel-based heterointerfacial nanocomposite.
5. The preparation method according to claim 4, wherein, In step 1), the transition metal salt is selected from at least one of ruthenium trichloride, platinum dichloride, and palladium dichloride; and / or, in step 1), the mass ratio of the metal-organic framework material to the transition metal salt is 1:0.1 - 1:
10. Preferably, in step 2), the reducing agent is selected from sodium borohydride and hydrazine hydrate; and / or, in step 2), the mass ratio of the reducing agent to the metal-organic framework material loaded with transition metal ions is 1:0.1 - 1:
50. Preferably, in step 3), the electroless nickel plating solution includes nickel chloride, sodium citrate, maleic acid, sodium hydroxide, and deionized water; in the electroless nickel plating solution, the concentration of nickel chloride is 5 mg / mL - 40 mg / mL; the concentration of sodium citrate is 10 mg / mL - 50 mg / mL; the concentration of maleic acid is 1 mg / mL - 20 mg / mL; the concentration of sodium hydroxide is 5 mg / mL - 30 mg / mL; and / or, in step 3), the reaction time is 1 - 4 hours, and the reaction temperature is 70 - 90 °C. Preferably, in step 4), the chemical bath solution includes transition metal salt, sodium citrate, maleic acid, sodium hydroxide, and deionized water; in the chemical bath solution, the concentration of the transition metal salt is 2.5 mg / mL - 20 mg / mL; the concentration of sodium citrate is 5 mg / mL - 25 mg / mL; the concentration of maleic acid is 0.5 mg / mL - 10 mg / mL; the concentration of sodium hydroxide is 1 mg / mL - 15 mg / mL; and / or, in step 4), the reaction time is 1 - 4 hours, and the reaction temperature is 70 - 90 °C.
6. The preparation method according to claim 4 or 5, wherein In step 5), the mass ratio of the activator to the amino group-containing covalent organic framework monomer is 20:1 - 80:1; and / or, in step 5), the mass ratio of the metal-organic framework material loaded with nickel metal nanoparticles and transition metal nanoparticles to the amino group-containing covalent organic framework monomer is 1:1 - 20:1; And / or, in step 6), the mass ratio of the covalent organic framework monomer containing an amino functional group to the covalent organic framework monomer containing an aldehyde functional group is 1:0.5 - 1:2; and / or, in step 6), the mass ratio of the activator to the covalent organic framework monomer containing an aldehyde group is 1:1 - 20:
1. And / or, in step 7), the addition amount of the covalent organic framework monomer containing an amino functional group is the same as that in step 5); and / or, the addition amount of the covalent organic framework monomer containing an aldehyde functional group is the same as that in step 6).
7. Use of the nickel-based heterogeneous interface nanocomposite according to any one of claims 1 - 3 in a microwave diagnosis and treatment preparation. Preferably, use of the nickel-based heterogeneous interface nanocomposite in a microwave hyperthermia preparation. Preferably, use of the nickel-based heterogeneous interface nanocomposite in a microwave dynamic therapy preparation.
8. Use of the nickel-based heterogeneous interface nanocomposite according to any one of claims 1 - 3 in a contrast agent.
9. A preparation, the preparation comprising the nickel-based heterogeneous interface nanocomposite according to any one of claims 1 - 3.
10. The preparation according to claim 9, wherein, The preparation is a microwave diagnosis and treatment preparation or a contrast agent. Preferably, the microwave diagnosis and treatment preparation is a microwave hyperthermia preparation or a microwave dynamic therapy preparation. Preferably, the microwave diagnosis and treatment preparation is a tumor microwave diagnosis and treatment preparation.